2014
DOI: 10.1089/thy.2013.0177
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphodiesterase 8B Gene rs4704397 is Associated with Thyroid Function, Risk of Myocardial Infarction, and Body Height: The Tromsø Study

Abstract: Objective: High serum thyrotropin (TSH) levels predict cardiovascular disease (CVD). Recently several single nucleotide polymorphisms (SNPs) associated with TSH levels have been identified, one of them being the rs4704397 SNP in the phosphodiesterase 8B (PDE8B) gene. If the relation between thyroid function and CVD is causal, one could also expect rs4704397 genotypes to predict CVD and possibly health in general. Methods: DNA was prepared and genotyping performed for rs4704397 in subjects who participated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Although Jorde et al (77) found no association between their investigated SNPs and myocardial infarction (among other outcomes), Levin et al (78) found that variations in the VDR gene may alter the association of 25(OH)D with major clinical outcomes, including myocardial infarction. While results of both studies were heavily supported by a large cohort size, their applicability to other populations is questionable on the basis that one study was confined to elderly white adults (78), whereas the other took place in Norway (77), the population of which does not possess a significantly lower 25(OH)D level compared to the rest of west Europe despite its latitude, and thus does not represent a vitamin D-depleted population. Nevertheless, it is abundantly clear that large-scale studies investigating different populations are warranted since SNPs in CYP2R1, CYP27B1 and DHCR7 have been associated with type 1 diabetes (79), warranting further investigations on diseases not covered by the previously conducted studies.…”
Section: Novel Perspectives I Genetic Variants In Vitamin D Homeostamentioning
confidence: 99%
“…Although Jorde et al (77) found no association between their investigated SNPs and myocardial infarction (among other outcomes), Levin et al (78) found that variations in the VDR gene may alter the association of 25(OH)D with major clinical outcomes, including myocardial infarction. While results of both studies were heavily supported by a large cohort size, their applicability to other populations is questionable on the basis that one study was confined to elderly white adults (78), whereas the other took place in Norway (77), the population of which does not possess a significantly lower 25(OH)D level compared to the rest of west Europe despite its latitude, and thus does not represent a vitamin D-depleted population. Nevertheless, it is abundantly clear that large-scale studies investigating different populations are warranted since SNPs in CYP2R1, CYP27B1 and DHCR7 have been associated with type 1 diabetes (79), warranting further investigations on diseases not covered by the previously conducted studies.…”
Section: Novel Perspectives I Genetic Variants In Vitamin D Homeostamentioning
confidence: 99%
“…PDE8 is a highly selective cAMP hydrolyzing enzyme and consists of two genes, PDE8A and PDE8B that due to alternative splicing processes, generate five splice variants: PDE8A1-PDE8A5 and PDE8B1-PDE8B5 [117,118] (Figure 8). Both PDE8 genes are widely expressed in all steroidogenic cell types with PDE8A mostly expressed in the testis and T-cells and PDE8B mainly distributed in the brain and thyroid gland making PDE8 a key player in T-cell activation, thyroid hormones production, sperm and Leydig cell functions and cardiac functions [119,120]. Several studies investigated the role of PDE8 in the whole testis.…”
Section: Pde8mentioning
confidence: 99%
“…Recently, another SNP was identified which is associated with TSH levels, namely the rs4704397 SNP in the phosphodiesterase 8B (PDE8B) gene [32]. A large number of subjects (8938) of the Tromsø Study who were without thyroid disease or thyroid medication were successfully genotyped for rs4704397.…”
Section: Genetic Variancementioning
confidence: 99%